Enhancing the Efficacy of Metal‐Free MRI Contrast Agents via Conjugating Nitroxides onto PEGylated Cross‐Linked Poly(Carboxylate Ester). Issue 14 (3rd June 2020) - Guo, Shiwei; Wang, Xiaoming; Dai, Yan; Dai, Xinghang; Li, Zhiqian; Luo, Qiang; Zheng, Xiuli; Gu, Zhongwei; Zhang, Hu; Gong, Qiyong; Luo, Kui
Abstract: Herein, two water‐soluble PROXYL‐based magnetic resonance imaging (MRI) macromolecular organic contrast agents (mORCAs) are designed and synthesized: linear and cross‐linked PCE‐mPEG‐Ppa‐PROXYL. They are prepared by conjugating linear and cross‐linked poly(carboxylate ester) (PCE) with poly(ethylene glycol) (mPEG2000 )‐modified nitroxides (PROXYL), respectively. Both mORCAs form self‐assembled aggregates in an aqueous phase and PROXYL is protected inside a hydrophobic core to achieve great resistance to reduction in the physiological environment, and they have low toxicity. Since cross‐linked PCE‐mPEG‐Ppa‐PROXYL possess a branched architecture, its self‐assembled aggregate is more stable and compact with a greater particle size. Cross‐linked PCE‐mPEG‐Ppa‐PROXYL outperform the linear one in the following aspects: 1) its longitudinal relaxivity ( r 1 = 0.79 mm −1 s −1 ) is higher than that of the linear one ( r 1 = 0.64 mm −1 s −1 ) and both excel the best mORCA reported so far ( r 1 = 0.42 mm −1 s −1 ); 2) its blood retention time (≈48 h) is longer than that of its linear counterpart (≈10 h); 3) cross‐linked PCE‐mPEG‐Ppa‐PROXYL provided better MR imaging contrast resolution in normal organs (liver and kidney) and tumor of mice than the linear one. Overall, cross‐linked PCE‐mPEG‐Ppa‐PROXYL may have great potential to be a novel metal‐free macromolecular contrast agent for MR imaging. Abstract : Two biodegradable PEGylated and nitroxides functionalized poly(carboxylate ester) are prepared. The cross‐linked polymer is superior to the linear one in terms of longitudinal relaxivity (0.79 vs 0.64 mm −1 s −1 ) and MR imaging in liver and tumor of mice, so it shows great potential to be a novel metal‐free macromolecular contrast agent for MR imaging.